Examination of socialization levels of university students engaging in individual and team sports - Devecioglu, Sebahattin; Sahan, Hasan; Yildiz, Mustafa; Tekin, Murat; Sim, Hatice (Elsevier Science Bv, 2012)
The objective of this study is to examine socialization levels of university students engaging in individual and team sports. 587 university students in total including 248 girls and 339 boys receiving education in various faculties and graduate schools of Dumlupinar University, Inonu University, Gazi University and 19 Mayis University constitute the research group. To achieve study objective, the socialization scale developed by Sahan (2007) was used. Significance was extracted P<0.05 by employing The Kolmogorov-Smirnov test and two-way ANOVA test in solution and interpretation of data. SPSS (Statistical package for social sciences) package software was employed in evaluation of data and finding the calculated values. As a result of this study, students, who are engaged in team sports, have higher socialization levels than students performing in individual sports. Besides, it was found that department and branch variable has an influence on socialization levels of students.
4th World Conference on Educational Sciences (WCES) -- FEB 02-05, 2012 -- Univ Barcelona, Barcelona, SPAIN
Keywords: Team Sport; Individual Sport; University Student; Socialization Introduction